Screening for Selected Club Drugs Utilizing LC/MS Direct Urine Analysis - Kourtesi, Eleni; Pistos, Constantinos; Papoutsis, Ioannis; Spiliopoulou, Chara; Athanaselis, Sotiris; Stefanidou, Maria (Current Pharmaceutical Analysis, 2015)
A simple liquid chromatography mass spectrometric method with direct urine injection analysis was developed and validated for the identification and quantification of gammahydroxybutyric acid (GHB), gamma-butyrolactone (GBL), 1,4-butanediol (1,4-BD), methylenedioxyn- methylamphetamine (MDMA), 3,4-methylenedioxy-amphetamine (MDA), 3,4-methylenedioxy-Nethylamphetamine (MDEA), ketamine (KET) and norketamine (Nor-KET). GHB-d6, GBL-d6, MDMA-d5, and KET-d4 were used as internal standards (IS). The method has the advantage of one step sample preparation which includes an appropriate dilution and filtration before its injection into the LC/MS system. The protonated ions of the analytes were detected and quantified using an ESI probe operating in positive mode and selected ion monitoring (SIM). The linear range was between 8-20 μg/mL for GHB, GBL and 1,4-BD, 50- 1000 ng/mL for MDEA, KET and Nor-KET and 250-1000 ng/mL for MDMA and MDA, providing square correlation coefficient (r2) ≥ 0.98. Interday and intraday errors were found to be ≤ 13.53%. The applicability of the proposed direct injection LC/MS method was confirmed with the analysis of ten authentic samples initially tested for amphetamines through a preliminary immunoassay screening. In addition, eight samples were assayed for KET and Nor-KET and six samples for GHB, GBL and 1,4-BD. The method is simple, accurate and possesses better specificity comparing to the immunoassay techniques, which make it suitable for screening purposes. It also presents the same or lower cost comparing to the respective immunoassay kit, where available. Toxicological laboratories may use the proposed method, overcoming thus the appeared false positive results (amphetamines) or the absence of immunoassay kits (GHB, GBL, 1,4-BD, KET, Nor-KET), avoiding also the use of increased cost instrumentation such as a liquid chromatography tandem mass spectrometry.
Keywords: mass spectrometry